Molecular biology : genes to proteins - Tropp, Burton E. (Jones & Bartlett Learning, 2012)
This is a comprehensive guide through the basic molecular processes and genetic phenomena of both prokaryotic and eukaryotic cells. Designed for undergraduate and first year graduate students, this multi-purpose text has been completely updated to include many important advances made in the field of molecular biology. Maintaining the original structure-function approach evident in the first two editions, this book provides students with an accessible overview of molecular biology before moving into more in-depth discussions. Broken into six sections, topics are strategically arranged to cover basic information that is necessary in understanding the more advanced topics focused on in later sections